Three representative UK moorland soils show differences in decadal release of dissolved organic carbon in response to environmental change - Stutter, M. I.; Lumsdon, D. G.; Rowland, A. P. (Biogeosciences, 2011)
Moorland carbon reserves in organo-mineral soils may be crucial to predicting landscape-scale variability in soil carbon losses, an important component of which is dissolved organic carbon (DOC). Surface water DOC trends are subject to a range of scaling, transport and biotic processes that disconnect them from signals in the catchment's soils. Long-term soil datasets are vital to identify changes in DOC release at source and soil C depletion. Here we show, that moorland soil solution DOC concentrations at three key UK Environmental Change Network sites increased between 1993–2007 in both surface- and sub- soil of a freely-draining Podzol (48 % and 215 % increases in O and Bs horizons, respectively), declined in a gleyed Podzol and showed no change in a Peat. Our principal findings were that: (1) considerable heterogeneity in DOC response appears to exist between different soils that is not apparent from the more consistent observed trends for streamwaters, and (2) freely-draining organo-mineral Podzol showed increasing DOC concentrations, countering the current scientific focus on soil C destabilization in peats. We discuss how the key solubility controls on DOC associated with coupled physico-chemical factors of ionic strength, acid deposition recovery, soil hydrology and temperature cannot readily be separated. Yet, despite evidence that all sites are recovering from acidification the soil-specific responses to environmental change have caused divergence in soil DOC concentration trends. The study shows that the properties of soils govern their specific response to an approximately common set of broad environmental drivers. Key soil properties are indicated to be drainage, sulphate and DOC sorption capacity. Soil properties need representation in process-models to understand and predict the role of soils in catchment to global C budgets. Catchment hydrological (i.e. transport) controls may, at present, be governing the more ubiquitous rises in river DOC concentration trends, but soil (i.e. source) controls provide the key to prediction of future C loss to waters and the atmosphere.